2020
DOI: 10.1038/s41419-020-2377-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 promotes angiogenesis and osteoblast differentiation by targeting HDAC7

Abstract: The regulation of bone formation and detailed mechanisms are still largely elusive, and the roles of microRNAs in this process have attracted much attention. Recently, a specific subtype of CD31 hi endomucin hi (CD31 hi EMCN hi) endothelium has been identified to promote bone formation, together with osteoblast development. However, the role of microRNA143 in the generation of CD31 hi EMCN hi endothelium and bone formation remains unknown. In this study, we found that miR-143 was expressed both in osteoblast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 40 publications
2
42
1
Order By: Relevance
“… 46 A number of miRNAs have been identified in the regulation of osteoblast differentiation. 47 , 48 , 49 These findings raise the possibility that osteogenic differentiation during bone remodeling can be regulated by miRNAs derived from bone cells. In our study, we identified that miR-324 was highly expressed in osteoclast-derived sEVs using miRNAs microarray analysis.…”
Section: Discussionmentioning
confidence: 94%
“… 46 A number of miRNAs have been identified in the regulation of osteoblast differentiation. 47 , 48 , 49 These findings raise the possibility that osteogenic differentiation during bone remodeling can be regulated by miRNAs derived from bone cells. In our study, we identified that miR-324 was highly expressed in osteoclast-derived sEVs using miRNAs microarray analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Osterix seems to be the direct target of miR-143 in suppressing osteogenic differentiation of MC3T3-E1 cells [ 37 ]. In miR-143 knockout mice, osteoblast differentiation was significantly inhibited [ 38 ]. All these data fit our results of high serum levels of miR-143-3p indicating a high risk of osteoporosis (OR 2.81).…”
Section: Discussionmentioning
confidence: 99%
“…The rabbits were housed in barrier housing conditions in the Animal Center of Fourth Military Medical University. Gengerate a rabbit osteoporosis model, we used the protocol as described previously ( 8 ). Briefly, we fasted the rabbits for 24 h prior to surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described ( 8 ). We used M-PER Protein Extraction Reagent (CST) supplemented with a protease inhibitor cocktail (CST) to lyse cells.…”
Section: Methodsmentioning
confidence: 99%